Association of a school-entry varicella vaccine requirement with the declining incidence of varicella infection - Borchardt, Stephanie M.; Hunt, Kae; Dworkin, Mark S. (Journal of Pediatric Infectious Diseases, 2008)
Varicella vaccine was licensed in the United States in March 1995. During 1995 to 2000, active surveillance sites observed a 71% to 84% decrease in cases of varicella infection. We describe an evaluation of the passive varicella surveillance system in Illinois including trends in the incidence of varicella and the impact of a school-entry vaccine requirement. Varicella surveillance data and varicella-specific hospital discharge data collected by the Illinois Department of Public Health (IDPH) during January 1995 through December 2005 were reviewed and summarized. IDPH received 29,189 aggregate reports representing 138,177 cases of varicella infection and 136 individual case reports. Incidence of varicella infection declined 95% from 2.0 cases per 1000 population in 1995 to 0.1 cases per 1000 population in 2005. Hospital discharge data also demonstrated a notable decline (78%). IDPH policy requiring vaccination of children ≥ 2 years of age enrolled in child care facilities or school-operated programs at or below the kindergarten level was temporally associated with a decline from 10,805 cases in 2002 to 3,829 cases in 2003 (65%). Widespread use of the varicella vaccine has resulted in a marked decline in cases of varicella infection, thereby decreasing the burden of reporting and increasing the feasibility of case-based reporting.
Keywords: Varicella vaccine; varicella incidence